Relationship between Expression of Vascular Endothelial Growth Factor and Cervical Lymph Node Metastasis in Papillary Thyroid Cancer： A Meta-analysis - 黄晓庆;何文山;张惠琼;杨瑞;黄韬 (Current medical science, 2017)
The aim of the present study was to examine the relationship between the protein expression of vascular endothelial growth factor（VEGF） and lymph node metastasis（LNM） in papillary thyroid cancer（PTC）. VEGF-related articles that had been published until August 2016 were searched from the Pub Med, EMBASE, and MEDLINE to identify the risk factors of LNM in PTC. Rev Man 5.3 software was used for the meta-analysis. Finally, 9 articles met the inclusion criteria and were included in our meta-analysis. LNM was found to be present in 176 of 318 patients（57.8%） with high VEGF expression and in 71 of 159 patients（47.0%） with low VEGF expression. The overall OR was 2.81（95% confidence interval, 1.49–5.29）. LNM occurred more frequently in patients with high VEGF expression than in those with low VEGF expression（P=0.001）. Heterogeneity was markedly decreased in the subgroup analyses of LNM in terms of the patients＇ country of origin and the detection methods. Our meta-analysis concluded that the VEGF protein expression is associated with LNM in PTC.